NERVE-2: A Three-Dimensional Patient Simulation of Oculomotor Nerve Palsy - Marc Peden; Joon Hao Chuah; Aaron Kotranza; Kyle Johnsen; Benjamin Lok; Juan Cendan (Association of American Medical Colleges, 2010)
Abstract This module portrays a simulated patient who presents to a clinic or emergency room with a complaint of double vision. The purpose of this simulation is to promote effective history taking and evaluation in order to identify a potentially life threatening cranial nerve disorder. A significant limitation of live standardized patient interaction is the difficulty in reproducing clinical findings in various conditions. Therefore, medical students are often taught diagnostic skills for evaluation of cranial nerve injuries in a low fidelity manner, mainly where the injury is described, and the student is able to visualize still images of the anticipated clinical findings. The current simulation incorporates not only an accurate depiction of the clinical findings, but an opportunity to dialogue with the patient to ascertain important history information. Once the user has completed their evaluation, they view a brief lesson plan that reinforces the pertinent history bullets and examination findings related to the pathology. Further, the plan goes on to briefly discuss the appropriate management of the patient. By the completion of this lesson, users should be comfortable identifying an oculomotor palsy and should consider the possibility of a life threatening condition such as a cerebral aneurysm. The module has been packaged to include all necessary resource files and materials. The learner should take approximately 30 minutes to complete the interaction and lesson plan. The program does have basic hardware and software requirements. This program was developed at the University of Florida, in conjunction with collaborators at both the University of Central Florida and the University of Georgia. It was implemented in the Florida curriculum for second-year medical students. The concept was to design a realistic patient interaction experience utilizing a virtual patient. The benefits of virtual patient interactions are numerous, and include standardization, opportunity for repeat interactions, and presentations of clinical findings that may be readily reproducible in human actors. By integrating the ability to perform a history and evaluate a realistic representation of the clinical examination findings, we anticipate a significant enhancement in medical student learning of various pathologies.